Correlation Between Clinicaland Pathological Characteristics of Henoch-Schönlein Purpura Nephritis in Adults (Iranian Journal of Kidney Diseases, 2017)
Introduction.Henoch-Schönlein purpura nephritis (HSPN) mainly affects children and is less common in adults, but its associated pathological changes are severe in adults, in whom it results in a poor prognosis. This study aimed to analyze the clinical and pathological characteristics of HSPN in adults and to identify the correlations among them. Materials and Methods. Clinical and pathological data from139 patients older than 18 years of age who had been diagnosed with HSPN and had received renal biopsy at our center from January 2012 to November 2014 were collected and were grouped according to the different conditions and analyzed retrospectively. Results. The 139 HSPN patients included 74 men and 65 women, with an average age of 39.17 ± 15.87 years. The pathological grade was IIIa in most of the patients, and moderate proteinuria was the most common clinical type. Kidney failure and 24-hour total urinary protein, serum uric acid, cystatin C, and β2-microglobulin levels were positively correlated with the pathological grade and activity (P < .05). Age, kidney failure, and uric acid were positively correlated with the pathological chronicity (P < .05). Conclusions. The clinical characteristics of the adult HSPN patients were correlated with the severity of the renal pathology. It is feasible to predict renal pathological changes according to the clinical manifestations of adult HSPN patients.